2016
DOI: 10.3390/su8070670
|View full text |Cite
|
Sign up to set email alerts
|

Geographical Variation of Climate Change Impact on Rice Yield in the Rice-Cropping Areas of Northeast China during 1980–2008

Abstract: Northeast China (NEC) is one of China's major rice production areas and has experienced obvious climate warming over the past three decades, similar to other mid-to high-latitude regions in the Northern Hemisphere. The present study investigates the temporal and spatial impacts of climate warming on rice yield in mid-high latitude regions. In this study, two time series datasets of rice yield and climate records in the NEC, including 178 county sites and 105 climate stations and covering the period from 1980 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…This suggests it could be possible to breed for a genotype optimized for the performance of all three of these traits by making crosses between accessions of these two clusters. Previous analysis has shown that the most productive rice systems worldwide tend to be at higher latitudes, where the plant can maximize productivity under longer daylength (Liu et al, 2016). Interestingly, the frequency distributions of accessions in Cluster 3 peaked at fewer days to maturity—indicating a shorter growing season—and at higher latitudes than the other two clusters (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests it could be possible to breed for a genotype optimized for the performance of all three of these traits by making crosses between accessions of these two clusters. Previous analysis has shown that the most productive rice systems worldwide tend to be at higher latitudes, where the plant can maximize productivity under longer daylength (Liu et al, 2016). Interestingly, the frequency distributions of accessions in Cluster 3 peaked at fewer days to maturity—indicating a shorter growing season—and at higher latitudes than the other two clusters (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…The considerable agro-irrigation activities are probably the main cause of the relatively lower correlation (Table 1), and lower coefficient of determination for both SPI and SPEI ( Table 2). The relative positive response of rice yield to drought conditions may be as explained by Liu et al [43] and Yin et al [21], who indicated that climate warming has made the crop growing season longer in Northeast China, which results in some high-yielding varieties with a longer growth duration. Table 2.…”
Section: Drought Impact On the Main Cereal Crop Yieldsmentioning
confidence: 99%
“…However, while farmers will take measures to reduce the harm of climate change to crops and reduce the negative impact of climate change, farmers will seize climate change opportunities and fully use its beneficial impact. Adjusting planting strategies during crop production and adopting appropriate management measures and technologies are inevitable choices for managing climate change [47].…”
Section: Theoretical Basismentioning
confidence: 99%